Development of Model to Improve Basic Technique in Playing Sepak Takraw - Arizky Ramadhan; Aprizal Fikri; iyakrus iyakrus (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
This study aims to: (1) to develop a learning model of sepak takraw material according to students' characteristics, (2) to measure the effectiveness of packing models that have been developed (3) to test the effectiveness of learning models that have been developed to improve basic technique sepak takraw skills. This research is a research and development consisting of two stages, they are: preliminary stage and development stage. The preliminary stage consisted of: observation and field study. The development stage consisted of: initial drafting, expert validation, small-scale trials, large-scale trials, the final products, and effectiveness tests. Expert validation involved 2 experts with delphi techniques. Field test design used times series design. Techniques using to collect the data was observation and interview. Data analysis to determine validity used Content Validity Ratio (CVR). Data analysis for effectiveness used Sample Paired t Test. The results of the development learning of sepak takraw were (1) the product of the learning model sepak takraw for student, (2) the implementation of a safe learning model, easy and fun to do and (3) the product is effective to improve the skills of sepak takraw students from psychomotor values. The results of expert assessment of the model product developing had a validation value of 1 entered in the eligible category. The result of analysis of the values got the result of significance of Sig2 tiled <0.5., the mean at test of effectivity psychomotor value of 6.6000 had increased to 7.5200. So it can be concluded that the model was affective to improve basic technique of students